SIMULAÇÃO DA ETAPA DE RESFRIAMENTO DA POLIAMIDA NO PROCESSO DE MOLDAGEM ROTACIONAL - Galera, Viviane Aparecida Verona (2007)
In rotomolding, cooling stage is of fundamental importance to optimize the process in terms of productivity and quality of rotomolded parts. Therefore, the present work has concentrated in the study of this process stage through computational simulation via the multi-purpose commercial software ANSYSTM . It uses finite element method being widely used in engineering problems involving structural and heat transfer analyses, among others. The rotomolding cooling simulation was based on polyamide 66, being its crystallization behavior determined by Differential Scanning Calorimeter (DSC). The effect of the crystallization was taken in account in cooling simulation by incorporation of heat of crystallization in enthalpy curve of the polyamide. The main aspect of present work was the incorporation in rotomolding simulation of the effect of air gap that forms between metallic mold and polymer during the cooling process. The simulations were carried out for different convection heat transfer coefficients of external cooling air, characterizing natural and forced convection. The results indicated that the air gap between polymer and mold has deep effect, decreasing cooling rate of polymeric part. This effect in the cooling rate was much more significant than the heat of crystallization of polymer. It was also more important than the variation of the convection heat transfer coefficient of external air. The simulations indicated also that this air gap can bring a great error if the mold temperature is used for monitoring the process by infrared thermometer. This occurs because the air gap presents an opposite effect in mold, increasing its cooling rate when formed. Simulations indicated the thickness of the air gap presents a significant effect on the temperature profiles of polymer and mold. The greater the thickness the greater the thermal gradient between mold and polyamide. In future works, the effect of crystallization in rotomolding cooling stage will be taken into account in simulation via Ansys by using the Nakamura equation. Thus, its kinetic parameters were calculated for the polyamide sample used in the present work. The Master Curve Approach vi was applied, having been obtained good results in description of the crystallization process of PA with the calculated kinetic parameters.